Nonresonant control of multimode molecular wave packets at room temperature - Murnane, M. M., author; Kapteyn, H. C., author; Leone, S. R., author; Weinacht, T. C., author; Bartels, R. A., author; American Physical Society, publisher (Colorado State University. Libraries, 2002)
We demonstrate the creation and measurement of shaped multimode vibrational wave packets with overtone and combination mode excitation in CCl4. Excitation of wave packets through nonresonant impulsive stimulated Raman scattering allows for coherent control of molecular vibrations without passing through an electronic resonance. This technique is therefore very general and can be implemented in a large class of molecular gases and liquids at STP, which were previously inaccessible because their resonances are in the VUV.